The investigation of didactic aspects of developing students’ english speaking skills at higher art schools of Ukraine - Костюк, Мирослава Павлівна (ScienceRise: Pedagogical Education, 2016)
The didactic principles of training and development of another language speaking skills of the students of higher art school are analyzed in the article. The dependency between the changes of value orientations in society and content of teaching-professional themes was outlined, the relation between the notions “communication” and “intercourse” and their role in communicative interaction was indicated. The main aim of research is in the analysis of the features of didactic aspects to facilitate and accelerate the comprehension of language by students of the higher art schools. The author underlines that communication is an important condition in the process of formation and development of both society and person. At the same time communication is the base of consciousness, cognition and social interaction for the solution of actual problems of reality. The series of didactic principles were separated: 1) improvement of teaching method by reorientation from pragmatic to communicative one; 2) modernization of the content of educational material; 3) guaranteeing of connection between teaching and extra-teaching activity in the process of speaking skills and abilities formation; 4) proper training of students for computer study and testing; 6) guaranteeing of integration of multicultural information with the main program material of professional academic disciplines. The author makes the conclusion that the observance of didactic principles in the study improves the quality of mastering English language by students and favors their ability to communicate